2017
DOI: 10.2337/db16-0816
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Disruption of Adenosine Kinase in Mouse Pancreatic β-Cells Protects Against High-Fat Diet–Induced Glucose Intolerance

Abstract: Islet β-cells adapt to insulin resistance through increased insulin secretion and expansion. Type 2 diabetes typically occurs when prolonged insulin resistance exceeds the adaptive capacity of β-cells. Our prior screening efforts led to the discovery that adenosine kinase (ADK) inhibitors stimulate β-cell replication. Here, we evaluated whether ADK disruption in mouse β-cells affects β-cell mass and/or protects against high-fat diet (HFD)–induced glucose dysregulation. Mice targeted at the Adk locus were bred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…Inhibition of ADK in β-cells has been shown to increase β-cell proliferation in vitro (Annes et al, 2012). Moreover, it has recently been shown that β-cell ADK knockout mice exhibit increased β-cell proliferation and insulin secretion in vivo, resulting in improvement of glycemia in mice exposed to the metabolic stress of a high-fat diet (Navarro et al, 2017). On the other hand, insulin secretion of islets from aged A 1 adenosine receptor knockout mice was enhanced compared with age-matched controls; this was associated with reduced oxidative stress and inflammation (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ADK in β-cells has been shown to increase β-cell proliferation in vitro (Annes et al, 2012). Moreover, it has recently been shown that β-cell ADK knockout mice exhibit increased β-cell proliferation and insulin secretion in vivo, resulting in improvement of glycemia in mice exposed to the metabolic stress of a high-fat diet (Navarro et al, 2017). On the other hand, insulin secretion of islets from aged A 1 adenosine receptor knockout mice was enhanced compared with age-matched controls; this was associated with reduced oxidative stress and inflammation (Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic removal of adenosine occurs either through its deamination by adenosine deaminase (ADA) to be converted to inosine or via phosphorylation by adenosine kinase (ADK) to form adenosine monophosphate [12,13]. As ADK plays a major role in adenosine removal and its availability for downstream effects, this adenosine-ADK balance is strictly regulated in healthy cells [14]. ADK has two isoforms: a long isoform, ADK-L, dominantly located in the nucleus [15]; and a short isoform, ADK-S, located in the cytoplasm [16].…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, the screening of small compounds using a primary β-cell replication assay or a human MYC (transcriptional regulator Myc-like) expression system identified that inhibition of at least two kinase targets, ADK and DYRK1A, can compensate for β-cell loss during type 1 or type 2 diabetes. 4 23 It is worth noting that whereas no glucose metabolism difference was found in adult mice, young-aged (4-week-old) Ins2-Cre ± Adk fl/fl mice improved glucose metabolism significantly. This difference in the observed glucose metabolism and β-cell mass between 4 and 9-12 weeks might be due to their age difference.…”
Section: Discussionmentioning
confidence: 97%
“…Our results exhibited that Ins2-Cre ± Adk fl/fl mice were more resistance to STZ-induced hyperglycaemia compared with their littermates. This resistance to STZ-induced hyperglycaemia was explained by significant increase of β-cell proliferation which was accompanied by Importantly, the Rip-Cre/Adk fl/fl and Ins1-Cre/ERT1 Lphi /Adk fl/ fl mice showed significantly improved glucose homeostasis under high-fat diet conditions, 23 which mostly mimic type 2 diabetes. In our study, we found that the specific loss of ADK in a β-cell causes Ins2-Cre ± Adk fl/fl mice to be more resistant to STZ treatment, a pathological model generally for type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%